Heterologous expression of an insecticidal gene from the armed spider (Phoneutria nigriventer) - Figueiredo,J. E. F. (2008)
Insect-pests are global problems that cause severe damage to crop plants, and their control is commonly based on chemical insecticides. However, negative effects of pesticides on the environment and human health emphasize the necessity to develop alternative methods for insect-pest control. In the present study, a gene coding for the insecticidal peptide TX4(6-1) of the Brazilian armed spider (Phoneutria nigriventer) was cloned in fusion with maltose binding protein (MBP) and expressed in Escherichia coli. The affinity purified protein MBP-GlyTX4 was cleaved with the Xa factor and used for a bioassay against Spodoptera frugiperda and rabbit immunization. Five micrograms GlyTX4 protein injected into the hemocoel of larvae and abdominal cavity of adults produced trembling and uncoordinated movements immediately after injection and all adult insects died after 12h. After two days, larvae became paralyzed and the epidermal color changed to dark brown. Furthermore, the development stage was prolonged for two weeks. Alternatively, slices of maize leaves were imbibed with 15 micrograms of the recombinant protein cleaved with the Xa factor and used as diet for larvae. In this experiment, all larvae died in about 30 minutes. Polyclonal antibodies anti-MBP-GlyTX4 were effective for recognizing MBP and GlyTX4 in whole cell extract from E. coli expressing the recombinant protein.